Evaluation of opioid-related deaths associated with opioid utilisation and the impacts of tramadol classification as a Schedule III Controlled Drug in the United Kingdom - Chen, Teng-Chou (2019)
In the past two decades, there has been a marked increase in opioid utilisation paralleled with the rising opioid mortality in many western countries. In contrast to opioid-overdose deaths in the United States which were mainly caused by opioid poisoning, the increasing opioid-related death in the United Kingdom (UK) involves a complex mechanism, including persistent opioid utilisation, medicines for chronic pain management and illicit drugs. However, no research has evaluated the association between opioid-related death, opioid utilisation and other determinants in the UK. In June 2014, tramadol was classified as a Schedule III controlled drug due to the concerns of increasing tramadol utilisation and tramadol-related deaths, but no research has evaluated the impact of the tramadol classification.